Clinical significance of soluble adhesion molecules in anti‐NMDAR encephalitis patients. Issue 5 (11th April 2019) - Ding, Yuewen; Yang, Chengjia; Zhou, Zheyi; Peng, Yu; Chen, Jinyu; Pan, Suyue; Xu, Hong; Cai, Yuping; Ou, Kaiyun; Xie, Wei; Wang, Honghao
Abstract: Increasing evidence indicates that immune system dysfunction affects anti‐N‐methyl‐D‐aspartate receptor (NMDAR) encephalitis. This study aims to investigate the relationship between adhesion molecules and the pathophysiology in anti‐NMDAR encephalitis. Soluble forms of Intercellular adhesion molecule‐1 (sICAM‐1), vascular adhesion molecule‐1 (sVCAM‐1), and L‐selectin (sL‐selectin), were measured in the CSF and serum of 26 participants with anti‐NMDAR encephalitis, 11 patients with schizophrenia and 22 patients with noninflammatory disorders. CSF levels of sICAM‐1, sVCAM‐1 and sL‐selectin were significantly elevated in the anti‐NMDAR encephalitis group. sVCAM‐1 levels were positively associated with modified Rankin scale score in anti‐NMDAR encephalitis patients at the onset and 3‐month follow‐up.